Elucidation Of The Mechanism Involved In The Proliferation And Migration Activity Of Cyperus Esculentus Lativum In Mda-Mb-231 And Mcf7 Breast Cancer Cell Lines - Seyram, Elom Achoribo (2019)
Cyperus esculentus L., is a tuber of family Cyperaceae which produces rhizomes from the base. It is used mostly as flour and oil in the food industry. In Ghana, it is mostly consumed raw as a snack because of its milky and sweet taste. The oil contains beta-sitosterol, oleic acid and quercetin, which are the compounds found to have anticancer property on various cancer cell lines. This research aimed to investigate the antiproliferative effect of the ethanolic and aqueous extracts of C. esculentus on MDA-MB-231 and MCF7 breast cancer cell lines. Also, the effects of the extracts on cell cycle progression and cell migration activity of both cell lines were studied. The possible mechanisms involved in the observed activity of the extract were also elucidated. MTT assay was run to check the extract effect on the viability of both cell lines, whereas flow cytometry was used to assess the cell cycle progression. Wound healing and Matrigel assays were run to check the cell migration activity, whereas qPCR and western blotting were run for gene and protein expressions, respectively. The results show that C. esculentus extracts only reduced the cell viability to 60 % at 24 hours and 80 % at 48 hours of treatment in MDA-MB-231 and MCF7, respectively. Prolong treatment and increase concentration did not affect the cell viability further.